Association of immigration background with kidney graft function in a publicly funded health system: a nationwide retrospective cohort study in Italy. (22nd July 2020) - Grossi, Alessandra Agnese; Maggiore, Umberto; Puoti, Francesca; Grossi, Paolo Antonio; Picozzi, Mario; Cardillo, Massimo
Summary: The impact of immigration background on kidney graft function (eGFR) is unknown. Italy has a publicly funded health system with universal coverage. Since immigration from non‐European Union (EU) countries beyond Eastern Europe is a recent and extensive phenomenon, Italy is a rather unique setting for studying the effect of immigration status as a socioeconomic and cultural condition. We retrospectively identified all adult deceased donor kidney transplant recipients (KTRs) in Italy (2010–2015) and followed them until death, dialysis or 5‐years post‐transplantation; 6346 were EU‐born, 161 Eastern European‐born, and 490 non‐European‐born. We examined changes in eGFR after 1‐year post‐transplant using multivariable‐adjusted joint longitudinal survival random‐intercept Cox regression. Compared to EU‐born KTRs, in non‐European‐born KTRs the adjusted average yearly eGFR decline was −0.96 ml/min/year (95% confidence interval: −1.48 to −0.45; P < 0.001), whereas it was similar in Eastern European‐born KTRs [+0.02 ml/min/year (−0.77 to +0.81; P = 0.96)]. Adjusted 5‐year transplant survival did not statistically differ between non‐European‐born, Eastern European‐born, and EU‐born. In those surviving beyond 1‐year, it was 91.8% in EU‐born (87.1–96.8), 92.5% in Eastern European‐born (86.1–99.4), and 89.3% in non‐European‐born KTRs (83.0–96.0). This study provides evidence that among EU KTRs, non‐European immigration background is associated with eGFR decline.